Repurposing amine and carboxylic acid building blocks with an automatable esterification reaction. Issue 8 (4th January 2023) - McGrath, Andrew; Zhang, Rui; Shafiq, Khadija; Cernak, Tim
Abstract : We present a robust deaminative esterification reaction between an alkyl pyridinium salt and carboxylic acid, as complement to the venerable amide coupling. The scope of this reaction is further demonstrated with a robot-assisted library synthesis. Abstract : New methodologies to unite amines and carboxylic acids that complement the popular amide coupling can significantly expand accessible chemical space if they yield products distinct from the classic R–NHC(O)–R′ amide arrangement. Here we have developed an amine–acid esterification reaction based on pyridinium salt activation of amine C–N bonds to create products of type R–OC(O)–R′ upon reaction with alkyl and aryl carboxylic acids. The protocol is robust and facile as demonstrated by automation on open-source robotics.